Resistance training in patients with limb‐girdle and becker muscular dystrophies. Issue 2 (21st November 2012) - Sveen, Marie‐Louise; Andersen, Søren P.; Ingelsrud, Lina H.; Blichter, Sarah; Olsen, Niels E.; Jønck, Simon; Krag, Thomas O.; Vissing, John
Abstract Introduction: In this study we investigated the effect of strength training in patients with limb‐girdle muscular dystrophy (LGMD) and Becker muscular dystrophy (BMD). Methods: In 2 studies we compared the effect of low‐intensity training (LOIT; n = 8) and high‐intensity training (HIT; n = 4) in muscles of the upper and lower extremities. Patients were tested for maximal strength and endurance before and after the training program. Results: LOIT training over 6 months resulted in increased biceps strength and endurance. HIT training increased endurance and strength in wrist flexion and extension and in elbow flexion. One patient discontinued HIT training due to muscle soreness and mildly increased plasma CK levels without strength deterioration. Conclusions: Both LOIT and HIT increased muscle strength and endurance in some of the muscles tested and were well tolerated in most patients. Our findings suggest that supervised resistance training may be considered in the management of patients with LGMD2 and BMD. Muscle Nerve, 2013